ANALYSIS OF THE REUSE OF COCONUT WASTE WATER FOR KANGKONG USING A VERTICAL CULTURE HYDROPONIC SYSTEM - Kasman, Monik; Riyanti , Anggrika; Febby Valency, Amelia; Hasan, Hadrah (Journal of Data Analytics, Information, and Computer Science, 2024)
Coconut wastewater is the by-product of the coconut milk store. It contains BOD of 9.908,41 mg/L and COD of 38.264,73 mg/L. It can pollute when it is discharged into received water directly. Pollution can prevented by wastewater treatment using phytoremediation method and wastewater reuse for hydroponic crops. This study aimed to determine the effectiveness of the hydroponic system in reducing BOD and COD concentration of coconut wastewater, the effect of the reuse coconut wastewater on crop growth, and to analyze the suitability of coconut wastewater with hydroponic’s standard nutrients. The crop selected in this study was Kangkong (Ipomoea reptans Poir) with a vertical hydroponic system. The retention time was determined based on the Day After Planting (DAP). The DAP ranged in 0 day, 7 days, and 14 days. The crop parameters observed in this study are height, the number of leaves, and gross weight, compared to the controlled crops that use hydroponic’s standard nutrients. The highest reduction of BOD (79,22%) and COD (82,76%) occurs on DAP of 7 days. Crop growth increased as BOD and COD decreased. Initial pollution concentration caused stunted growth, so that the measurement results of phytoremediation crops were below the controlled crops. Coconut wastewater is within the range of standard hydroponic nutrients with 6,16-7,62 pH value, 1.220-1.570 ppm TDS, 2.470-3.180 μS/cm EC, and 25-26oC temperature